Optimization of Carrier Distributions in Periodic Gain Structures toward Blue VCSELs. Issue 1736 (19th January 2015) - Kaplar, R.; Meneghesso, G.; Ozpineci, B.; Takeuchi, T.; Matsui, Kenjo; Horikawa, Kosuke; Kozuka, Yugo; Ikeyama, Kazuki; Komori, Daisuke; Takeuchi, Tetsuya; Kamiyama, Satoshi; Iwaya, Motoaki; et al.
ABSTRACT We have fabricated light emitting diodes (LEDs) in which two active regions separated with a Mg-doped GaN intermediate layer were placed in a single pn junction toward periodic gain structures (PGS) for blue vertical-cavity surface emitting lasers (VCSELs). By current density dependence on a emission intensity ratio from two different active regions, we obtained a very stable emission intensity ratio over 1 kA/cm2. This result is also confirmed with the simulation result. Furthermore, we found that the difference of emission wavelength affect the carrier injection and the emission intensity ratio. On the basis of this result, the optimized well-balanced Mg concentration in the intermediate layer for the two identical active regions were estimated approximately 5 x 1018 cm-3.